(untitled) (Research, Society and Development, 2025)
Objective: Establish the relationship between colon cancer survival, resected lymph nodes and their clinical and demographic characteristics. Methodology: This is an observational, retrospective, descriptive and cross-sectional study, based on the review of medical records. Results: The study reviewed 230 medical records of patients with colorectal cancer (CRC), more than half of whom were women between 50 and 75 years old. 71.3% of surgeries were elective, with 65.2% performed by videolaparoscopy, with the most common location being the rectosigmoid colon in 6 of 10 patients. Patients over 50 years had a higher median survival of 96 months. Survival was higher for tumors in the transverse colon, N0 and stage IIB. Most tumors were classified as T3 (54.8%) and N0 (53.9%). 90% of patients were in M0. Survival was higher in patients with 12 or more lymph nodes removed (88 months) compared with less than 12 (80 months). 89.6% did not receive neoadjuvant therapy, but among those who did, 9.1% used chemotherapy and radiotherapy. Chemotherapy was the adjuvant treatment in 52.6% of cases. Conclusion: CRC remains a health problem, with an increased incidence in younger patients. Overall survival is influenced by factors such as tumor location, sex, age, disease stage, and lymph node involvement. In the study, the removal of 12 or more lymph nodes did not provide a significant survival advantage, and the presence of metastatic lymph nodes worsened the prognosis. Lymphadenectomy remains essential in the curative treatment of CRC, allowing better staging and guidance for chemotherapy.